2002
DOI: 10.1097/01.asn.0000013296.11876.12
|View full text |Cite
|
Sign up to set email alerts
|

Low Tonicity Mediates a Downregulation of Cyclooxygenase-1 Expression by Furosemide in the Rat Renal Papilla

Abstract: Abstract. It is well known that loop diuretics enhance the renal excretion of prostanoids; therefore, this study aimed to characterize the influence of loop diuretics on the intrarenal expression of cyclooxygenases, which are the key enzymes for prostanoid formation. Male Sprague-Dawley rats were infused with furosemide (12 mg/kg per d) for 6 d, and the expression of cyclooxygenase-1 and -2 (Cox-1 and Cox-2) was analyzed in the different kidney zones. Furosemide increased Cox-2 mRNA expression approximately tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
11
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 36 publications
(71 reference statements)
4
11
0
Order By: Relevance
“…and body fluid volume on COX expression (3,44). Thus these findings support that COX-2-derived PGs participate in the regulation of urinary water excretion.…”
Section: Effect Of Dehydration On the Expression Of Cox-2 In Lithium-supporting
confidence: 70%
See 2 more Smart Citations
“…and body fluid volume on COX expression (3,44). Thus these findings support that COX-2-derived PGs participate in the regulation of urinary water excretion.…”
Section: Effect Of Dehydration On the Expression Of Cox-2 In Lithium-supporting
confidence: 70%
“…The downregulation of mRNA and protein levels was paralleled by a decrease in tissue PGE 2 concentrations in the papilla (3). Moreover, in vitro studies demonstrated that the expression of COX-1 mRNA changed in parallel with the changes in osmolality of the culture medium for IMCD cells (3), suggesting that the changes in interstitial osmolality may be a possible mediator of the effects of furosemide on the COX-1 expression. Similarly, lithium treatment reduces inner medullary interstitial osmolality (4) and urinary osmolality compared with controls.…”
Section: Changes In Cox-1 Cox-2 and Mpges Expression In Lithium-indmentioning
confidence: 98%
See 1 more Smart Citation
“…Changes in PGES expression were parallel to COX-1, and these parameters were further coordinated with an ϳ65% decrease in PGE 2 urinary output. Currently available data provide no specific mechanisms for these changes, and most data on COX-1 have come from studies in the renal inner medulla where tonicity appears to play a role in its regulation (6,23). Yet, the present conditions cannot easily be related with cortical cell volume or transport status.…”
Section: Discussionmentioning
confidence: 99%
“…PGE 2 synthesis in the collecting duct cells is modulated by osmolality (20). Along this line, it is consistently demonstrated that renal medullary COX-2 expression is induced by WD (13, 45); the opposite is true in that the COX-2 expression is reduced by water loading or chronic furosemide infusion that eliminates renal medullary osmotic gradient (4). Extensive in vitro studies have defined the signaling transduction pathway leading to osmotic regulation of COX-2 in collecting duct and renal medullary interstitial cells that primarily involve the activation of MAPK and NF-B (13,46).…”
Section: Discussionmentioning
confidence: 99%